Comparison of Different Diagnostic Method for Mycobacteria Tuberculosis in Suspected Patients - Khagi, AR; Singh, S; Subba, S; Bajracharya, A; Tuladhar, R; Lekhak, B; Shrestha, KB (Journal of Nepal Health Research Council, 2010)
Background: Microbial examination of smear of AFB by Z-N stain is currently the most rapid method for the detection of M. tuberculosis but its sensitivity is low i.e. required at least 10,000 bacterial cells per ml of sputum and also none specific, but auramine staining method has higher sensitivity than that of the Z-N stain but there are chances of false positive. Objective of this study was to find the correlation between chest X-ray, direct sputum smear examination by Ziehl-Neelsen stain, Auramine fluorochrome stain and sputum culture for M. tuberculosis. Methods: During that study period 250 x 3 samples were taken three each from 250 patients and divided into two groups A and B by performing Auramine fluorochrome stain in all samples . In group A, there were 150 fluorochrome stain positive samples. One each from 150 patient for comparative study of direct sputum smear examination by Ziehl-Neelsen stain, , culture on LJ medium and chest X-ray. Similarly in group B, next 100 fluorochrome stain negative specimens one each from 100 patients were taken for the comparative study of direct sputum smear examination by Ziehl-Neelsen stain, culture and chest X-ray. Results: In the study group A (n=150) all the specimens were positive in Auramine fluorochrome stain and all of them show positive in X-ray but only 134 showed positive in Ziehl-Neelsen stain and 136 showed positive in culture. In the study group B (n=100), all the specimens were negative in Auramine fluorochrome stain and all of them show negative in Ziehl-Neelsen stain but 14 of them were positive in culture and 24 were positive in chest X-ray. Conclusions: The diagnosis of PTB could be made by Auramine fluorochrome microscopy and culture. Key words: auramine fluorochrome stain; culture; mycobacterium tuberculosis; x-ray; ziehl-neelsen. DOI: 10.3126/jnhrc.v7i2.3012 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 84-88